Understanding islamic finance concepts through innovative game: name the riba transaction! / Azilawati Banchit ... [et al.] - Banchit, Azilawati; Zainuddin, Puteri Faida Alya; Lai, Tze Wee (2021)
The main idea of this innovative stick, card and cup game, (adapted from the method in the award winning Name the Numbers!©) is to educate the players to classify the financial transaction items which are permissible or non-permissible in the shariah principles. Lack of understanding in the shariah Arabic terms or its concepts may hinder people, especially the Muslims to adopt Islamic finance as their way of life despite knowing that dealing with interests are very much the basis of conventional finance transactions. Hence, this motivates for the game called Name the Riba Transaction!© to be innovated to help more people to understand the shariah concepts in a fun and interesting way. A small focus group interview was done for a thematic analysis where the findings managed to answer the main research questions whether the game can help to understand the concepts of riba and gharar to the players. Few themes were reported were derived from the respondents after playing the game which are ‘better understanding’, ‘ knowledge into practical’ and how the game is “promotable” to other people.